Sediments of time : on possible histories - Koselleck, Reinhart (Cultural memory in the present., 2018)
This new collection of previously untranslated essays by renowned German conceptual historian and theorist Reinhart Koselleck provides new insight into his theory of history, an ambitious attempt to unearth the conditions of all possible histories.